Peta dan Persoalan Keselarasan Matematis al-Qur’ān - Izza Rohman (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2012)
This essay highlights numerous serious efforts made in the last decades to find out mathematical miracles of the Qur’ān. While it recognizes that some of the findings resulted from these efforts might be problematic in terms of accuracy, methodological consistency and even legitimacy, this essay emphasizes the potential of these inquiries to enrich the academic discourse on miraculous aspects of the Qur’ān (i‘jāz al-Qur’ān) -an already longstanding subject in the ‘ulūm al-Qur’ān. Mapping the approaches to put the Qur’ānic mathematical miracles into some broad categories, and giving a glimpse into its history and underlying assumptions, the essay examines some theological, epistemological and methodological issues in each category, pointing out some reasons to either appreciate or criticize these approaches.DOI: 10.15408/ref.v13i2.899